A comparative study of insect diversity and distribution across elevations at Denai Cadamba, UiTM Puncak Alam, Malaysia - KHAIRUDIN NURUL FATHIAH; ISKANDAR MUDA DINDA PUTRI ALHAFIZA; IBRAHIM NUR AMIN; MD YUSOF NUR NADIAH; MOHD HATTA SITI KHAIRIYAH; ABD WAHAB NOOR AKMAL; MOHD ZAZI NORHAFIZAH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Fathiah KN, Alhafiza IMDP, Amin IN, Khairiyah MHS, Akmal AWN, Norhafizah MZ. 2024. A comparative study of insect diversity and distribution across elevations at Denai Cadamba, UiTM Puncak Alam, Malaysia. Biodiversitas 25: 3473-3479. Insects play a significant role in shaping the ecosystem community and are beneficial to mankind in many ways. They are known for many roles such as pollinators, bioindicators, scavengers, and vectors for diseases. A study on the diversity and distribution of class Insecta was conducted using two Malaise traps at the hiking trail of Denai Cadamba, UiTM Puncak Alam, Malaysia as no study has been done here before. Two study sites with two different elevations were chosen: low elevation (70 meters above sea level/masl) and high elevation (110 masl). A total of 2476 individuals from 335 morphospecies belonging to 13 orders were collected. The orders identified were Diptera, Lepidoptera, Hymenoptera, Coleoptera, Hemiptera, Collembola, Thysanoptera, Orthoptera, Blattodea, Microcoryphia, Isoptera, Mantodea, and Psocoptera. Diptera was the most common order sampled, while Microcoryphia and Psocoptera recorded the least number, with only two individuals found each. The Shannon-Wiener Diversity Index (H?) showed that the higher elevation (trap 2) has a higher diversity with H?=1.362 compared to the lower elevation (trap 1) with H?=1.017. The Evenness Index (E?) and Margalef Richness Index (R?) were also higher for trap 2 with the values E?=0.300 and R?=1.635 respectively, while for trap 1, the values were E?=0.276 and the R?=1.315, respectively. Mann-Whitney test showed that there was a significant difference in the insect distribution between the low elevation and the high elevation with P<0.05. In general, this study found that the order distribution differs across the elevations. This might be due to the rainy season, sunlight exposure, warmer conditions, less human disturbance, and type of vegetation. The data obtained in this study can be used as a baseline for future research while serving as an educational purpose to create awareness among the public about insect conservation and management.